1977
DOI: 10.1128/aac.12.1.51
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the Curative Antimalarial Activities and Toxicities of Primaquine and Its d and l Isomers

Abstract: This investigation was undertaken to determine whether either d-primaquine or l-primaquine has sufficient advantage over primaquine to warrant evaluation for curative activity in human volunteers infected with Plasmodium vivax. It was found: (i) that the capacities of the isomers and the racemate to cure infections with Plasmodium cynomolgi in rhesus monkeys were essentially identical; (ii) that the subacute toxicities of the isomers and racemate for this monkey were qualitatively the same, but that l-primaqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 14 publications
7
48
1
Order By: Relevance
“…The finding of similar and relatively moderate inhibition of MAO A and B in vitro by 1A and 1B (Ki ranges 103-225/~M), enhanced 10-90-fold with 4, does not strongly support the concept that MAO A and B could catalyze their deamination to 3 in vivo at drug concentrations that give schizontocidal activity. Comparison of the optical isomers 1A and 1B of primaquine, favouring here the (-) isomer 1B as the less toxic compound, is offset by earlier reports showing that the (+) isomer 1A had a better therapeutic index in rhesus monkeys [16], with both 1A and 1B similarly inhibiting drug metabolism [17]. In view of the appearance of new and much improved antimalarials for radical cure and clearing of tissue parasites, such as 4 [12] or its 4-methyl-substituted analogues [18], further development of either (-)-primaquine (1B) or its (+) isomer 1A does in our opinion not seem warranted.…”
Section: Resultscontrasting
confidence: 77%
“…The finding of similar and relatively moderate inhibition of MAO A and B in vitro by 1A and 1B (Ki ranges 103-225/~M), enhanced 10-90-fold with 4, does not strongly support the concept that MAO A and B could catalyze their deamination to 3 in vivo at drug concentrations that give schizontocidal activity. Comparison of the optical isomers 1A and 1B of primaquine, favouring here the (-) isomer 1B as the less toxic compound, is offset by earlier reports showing that the (+) isomer 1A had a better therapeutic index in rhesus monkeys [16], with both 1A and 1B similarly inhibiting drug metabolism [17]. In view of the appearance of new and much improved antimalarials for radical cure and clearing of tissue parasites, such as 4 [12] or its 4-methyl-substituted analogues [18], further development of either (-)-primaquine (1B) or its (+) isomer 1A does in our opinion not seem warranted.…”
Section: Resultscontrasting
confidence: 77%
“…Studies in mice indicated that the subacute toxicity of l-PQ is 3-5 times higher than that of d-PQ and 2 times less than PQ. The acute single-dose toxicity of the d-PQ was at least 4 times as toxic as l-PQ [98,99]. It is noteworthy that PQ is not a racemic mixture, because l isomer prevails over the d isomers.…”
Section: A Yet Unveiled Mechanism Of Actionmentioning
confidence: 94%
“…As PQ has a stereogenic centre, it would be expectable that each isomer had different activities, considering the most probable involvement of enzymes in the drug's mechanism of action. Many scientists defended that PQ isomers have similar activity, based on the fact that both presented identical capacity for the radical cure of rhesus monkeys infected with sporozoites of P. cynomolgi [98]. Studies in mice indicated that the subacute toxicity of l-PQ is 3-5 times higher than that of d-PQ and 2 times less than PQ.…”
Section: A Yet Unveiled Mechanism Of Actionmentioning
confidence: 99%
“…However, the (+)-enantiomer is significantly more toxic than the (-)-enantiomer. In the rodent model described in [45,46], the (+)-enantiomer was more toxic than the (-)-enantiomer. The (-)-enantiomer of primaquine is transformed preferentially by mitochondrial enzymes though α-oxidation to (-)-carboxyprimaquine, which has a relatively low toxicity [47].…”
Section: The Difference Between Antimalarial and Toxic Activities Of mentioning
confidence: 99%